Chronic lymphocytic leukemia transformation into high‐grade lymphoma: a description of Richter's syndrome in eight dogs. (14th October 2015) - Comazzi, S.; Martini, V.; Riondato, F.; Poggi, A.; Stefanello, D.; Marconato, L.; Albonico, F.; Gelain, M. E.
Abstract: Richter's syndrome (RS) is the development of an aggressive lymphoma in patients with chronic lymphocytic leukaemia (CLL). In humans, RS occurs in 2–20% of CLL, which transform into diffuse large B‐cell lymphoma but reports in dogs are scarce. This study retrospectively describes eight dogs with CLL progressing into RS. A database including 153 dogs with CLL (93T CD8+ and 55 B‐CLL) was interrogated and RS was demonstrated in eight cases (representing 5.2% of total CLL): two with T‐cell (2.2% of T CLL) and six with a B‐cell immunophenotype (10.9% of B‐CLL). When RS occurred, lymphocytes were decreased compared to CLL. Five dogs had anaemia and two dogs thrombocytopenia. Frequent clinical signs included lymph node swelling, coughing, vomiting, neurological signs and weight loss. Independently from the therapy, RS was associated with a short survival (median 41 days). RS should be considered as an unfavourable evolution in canine CLL.